Seroprevalence of selected viral, bacterial and parasitic infections among inpatients of a public psychiatric hospital of Mexico - Alvarado-Esquivel, Cosme; Arreola-Valenzuela, Miguel Ángel; Rodríguez-Briones, Alfredo; Alanís-Quiñones, Olga Patricia; Estrada-Martínez, Sergio; Luevanos-Becerra, Carlos; Martínez-Saenz, Luis Felipe; Martínez-García, Sergio Arturo; Ramírez-Valles, Eda Guadalupe; Ibarra-Torres, Isaac; González-Verdín, Cesar Arnulfo (Revista do Instituto de Medicina Tropical de São Paulo, 2008)
We sought to determine the frequency of serological markers of selected infections in a population of psychiatric patients in Durango City, Mexico, and to determine whether there are any epidemiological characteristics of the subjects associated with the infections. One hundred and five inpatients of a public psychiatric hospital of Durango were examined for HBsAg, anti-HCV antibodies, anti-HIV antibodies, anti-Brucella antibodies, rapid plasma reagin and anti-Cysticercus antibodies by commercially available assays. Anti-Cysticercus antibodies were confirmed by Western blot and HBsAg by neutralization assay. Epidemiological data from each participant were also obtained. Seroprevalences of HBsAg, anti-HCV, anti-HIV, anti-Brucella, rapid plasma reagin and anti-Cysticercus antibodies found were 0.0%, 4.8%, 0.9%, 0.0%, 1.9%, and 0.9%, respectively. Overall, 9 (8.6%) inpatients showed seropositivity to any infection marker. We concluded that our psychiatric inpatients have serological evidence of a number of infections. HCV is an important pathogen among our psychiatric inpatients. Health care strategies for prevention and control of infections in Mexican psychiatric patients should be considered. Procuramos determinar a frequência de marcadores sorológicos de infecções em pacientes psiquiátricos da cidade de Durango, México e determinar se existem características epidemiológicas dos pacientes que podem ser associados a estas infecções. Cento e cinco pacientes internados neste hospital psiquiátrico de Durango foram examinados para HBsAg, anticorpos anti-HCV, anticorpos anti-HIV, anticorpos anti-Brucella, reaginas plasmáticos imediatas e anticorpos anti-Cysticercus por testes comerciais. Os anticorpos anti-Cysticercus foram confirmadoss por Western Blot e o HbsAg por testes de neutralização. Dados epidemiológicos de cada participante foram também obtidos. Soroprevalências encontradas de HbsAg, anti-HCV, anti-HIV, anti-Brucella, reagina plasmática imediata e anticorpos anti-Cysticercus foram respectivamente 0,0%, 4,8%, 0,9%, 0,0%, 1,9% e 0,9%. No conjunto, 9 (8,6%) de pacientes internados mostraram soropositividade para marcador infeccioso. Concluímos que nossos pacientes psiquiátricos internados têm evidência sorológica de infecções. HCV é um patógeno importante entre os pacientes psiquiátricos internados. Estratégias de saúde pública para prevenção e controle de infecções em pacientes psiquiátricos do México devem ser consideradas.